Investigating the effect of knowledge, attitude, and social marketing mixes on the behavior of consumption herbal medicines by patients - Mahdi Amraei; Effat Jahanbani Veshareh; Kambiz Ahmadi Angali; Amin Torabipour (Payesh)
Objective (s): Analyzing the behavior of herbal medicine users is essential for properly managing the herbal medicine industry. Therefore; this study was conducted to investigate the effect of knowledge, attitude, and social marketing mix strategies on patients' behavior in consuming herbal medicines. Methods:  This was a cross-sectional study that conducted from September 1, 2021, to March 20, 2022, in Ahvaz, Iran. Its statistical population included all patients. The sample of 244 patients was selected based on Cochran's formula. A self-designed questionnaire was used to collect data. Descriptive and analytical statistics including Pearson's correlation coefficient, one-way analysis of variance, linear regression and t-test were used for data analysis with the help of SPSS26 software. Results: The results showed that there was a significant relationship between the variables of social marketing strategy, knowledge and attitude of patients with their consumption behavior (p=0.001). Patients' attitude had the strongest positive relationship (r=0.579). Based on linear regression analysis, attitude, knowledge and place as the three main predictive factors had a positive effect on patients' consumption behavior. Also, there was a significant relationship between patients' consumption behavior and their insurance coverage (p=0.003) Conclusion: Any change in the level and correct use of herbal medicines requires a change in the knowledge and attitude of patients and the development of efficient and effective social marketing strategies, especially considering the place.